Pengembangan Nanoemulsi dari Bahan Alam Famili Anacardiaceae sebagai Sistem Penghantaran Senyawa Aktif Antibakteri: Narrative Review - Loisa Nopratity Reza; Afriyani Afriyani; Atri Sri Ulandari; Ramadhan Triyandi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Antibiotic resistance has become a major global health concern, prompting the exploration of natural antibacterial agents and advanced drug delivery systems. Plants from the Anacardiaceae family are known to contain various bioactive compounds, such as phenolics, flavonoids, terpenoids, and fatty acids, which exhibit antibacterial properties. However, the effectiveness of these compounds is often limited by poor solubility and stability. This study aimed to analyze the development of nanoemulsion formulations derived from Anacardiaceae plants as antibacterial delivery systems through a narrative review approach. Literature was collected from NCBI and Google Scholar databases using relevant keywords, resulting in six eligible research articles published between 2016 and 2025. The findings indicate that nanoemulsions produced using both high-energy and low-energy methods exhibit droplet sizes within the nanometer range, with low-energy methods generally producing smaller and more homogeneous droplets. Nevertheless, antibacterial activity varied from weak to strong depending on plant species and bioactive composition, and was not directly correlated with droplet size alone. Overall, nanoemulsions enhance the stability and delivery of bioactive compounds, but their antibacterial effectiveness is strongly influenced by formulation optimization and the type of active compounds. These findings highlight the importance of systematic formulation strategies in developing effective natural antibacterial nanoemulsions Keywords: Anacardiaceae, Antibacterial activity, Nanoemulsion